Mental Stress, Anxiety and Depressive Symptoms and Interleuken-6 Level among Healthcare Workers during the COVID-19 Pandemic - Shaimaa A. A. M. Amer; Ahmed Mahmoud Fouad; Mohamed El-Samahy; Asmaa A. Hashem; Abdullah A. saati; Anas A. Sarhan; Maha Anani (SAGE Publishing, 2021)
Objectives This study aimed to evaluate the interleukin-6 (IL-6) levels and its relationship to stress, anxiety, and depressive symptoms among healthcare workers (HCWs) compared to controls during the COVID-19 pandemic. Methods A total of 80 HCWs in Suez Canal University Hospital in Ismailia, Egypt, and 80 controls were analyzed during the COVID-19 pandemic. The Depression, Anxiety and Stress Scale (DASS 21) questionnaire was used, and serum IL-6 level was determined in both groups. Results IL-6 levels were high in 81.2% (65) of HCWs compared to 36% (45) of controls ( P  < .05). The DASS score was higher in participants with high IL-6 levels (>3 ng/mL) than in those with mild to moderate levels ( P  < .05). The regression model revealed that the type of work as a healthcare staff, irregular or night shift, and stress were predictors of increased IL-6 levels among the studied sample ( P  < .05) (odds ratio = 20.30, 2.44, and 2.04, respectively). Conclusion The IL-6 level and DASS score were higher in HCWs compared to those in controls during the COVID-19 pandemic. The type of work as a healthcare staff, stress, and irregular or night shift were predictors of increased IL-6 levels.